Auditory sensory gating in Huffaz using an auditory brainstem response with a psychological task: a preliminary investigation - Dzulkarnain, Ahmad Aidil Arafat; kamal Azizi, Amirah; Sulaiman, Nur Hafizah (Elsevier Science Direct, 2020)
Objective